Algorithmic game theory : 11th International Symposium, SAGT 2018, Beijing, China, September 11-14, 2018, Proceedings /: 11th International Symposium, SAGT 2018, Beijing, China, September 11-14, 2018, Proceedings. (2018) - Unknown
No abstract available